(untitled) - Williams, B. R. (London, 1967)
This book introduce the research gap and European growth. The conditions of industrial innovation. The evaluation of industrial research. Assessing the economics of innovation, technical innovation...
Keywords: Technology,Công nghệ; Investment policy,Chính sách đầu tư